Elevation of Cardiac Biomarkers in COVID-19 As a Major Determinant for Mortality: A Systematic Review - Tracy Anabella Hermansyah; Eka Ginanjar; Valerie Hirsy Putri (Acta Medica Indonesiana)
Background: This study aimed to summarize the prognosis of Corona Virus Disease 2019 (COVID-19) patients with elevated troponin and N-terminal pro brain natriuretic peptide (NT-proBNP) levels and demonstrate the involvement of myocardial injury as a complication in COVID-19. Methods: A systematic literature search was performed using several databases (PubMed, MEDLINE, PROQUEST and SCOPUS ) for studies published up to August 2020. Observational studies about the mortality outcome of COVID-19 patients who experienced cardiac injury, as defined by the elevation of serum levels of troponin, brain natriuretic peptide (BNP), with NT-proBNP or only BNP or only NT-proBNP, were included. In addition, a critical appraisal was conducted for all included studies using the Critical Appraisal for Prognostic Studies checklist published by the Centre for Evidence-Based Medicine by the University of Oxford. Results: Seven retrospective observational studies fulfilled the inclusion criteria. This study found that there is a higher risk of death in COVID 19 patients with higher levels of troponin and NT-proBNP, indicating the importance of these biomarkers as determinant factors to predict in-hospital deaths. Conclusion: Based on the analysis, elevation of troponin  and NT-proBNP levels plays an essential role in determining the patient prognosis because it is shown to be associated with in-hospital mortality. This also supports the involvement of myocardial injury as a prominent fatal complication in COVID-19.